Síndrome de Ehlers-Danlos en pacientes con hiperplasia suprarrenal congénita portadores de la deleción del gen CYP21A2 - Notaristefano, Guillermo Jorge (2021)
Context: The contiguous gene deletion syndrome, CAH-X, was reported in a 15,6% of congenital adrenal hyperplasia (CAH) (Lao Q et al, 2019) and a 62,8% of CYP21A2 deletion carrier patients with TNXA/TNXB chimera (Gao Y et al, 2020). This results in deletions of CYP21A2 gene (30-kb deletion), encoding 21-hydroxylase necessary for cortisol biosynthesis, and contiguous deletion that extended into TNXB gene, which encodes the extracellular matrix glycoprotein tenascin-X (TNX). There are three TNXA/TNXB chimeras or gene conversions identified that differ in the junction site. CAH-X chimera 1 (CH-1) has TNXB exons 35?44 replaced with TNXA pseudogene and is characterized by the presence of the c.11435_11524+30del variant, CAH-X chimera 2 (CH-2) has TNXB exons 40?44 replaced with TNXA and is characterized by the TNXA derived c.12174C>G variant (Morissette R et al, 2015), and CAH-X chimera 3 (CH-3) has TNXB exons 41?44 replaced by TNXA and is characterized by the presence of three TNXA derived missense variants (Chen W et al, 2016). These chimeras results in TNXB haploinsufficiency or dominant negative effect and an Ehlers-Danlos Syndrome (EDS) phenotype. CAH-X syndrome has been described in monoallelic and biallelic forms (Chen W et al, 2016). Patients with known CAH-X syndrome should have a clinical evaluation to follow-up and prevent some severe events, as cardiac outcomes.\nObjective: The aim of this study was to develop a molecular strategy to analyze copy number variations and genetic status of TNXB gene in cohort of CAH patients carriers of CYP21A2 deletion to estimate the frequency of TNXB alterations in our population and perform clinical evaluation for EDS.\nMaterials and methods: A total of 66 unrelated CAH patients (44 females, 22 males, aged 4 days-36 years) carriers of CYP21A2 gene deletion (73 alleles), 43 parents and 8 siblings were screened for TNXB defects. All these 117 subjects were analyzed for CH-1 by MLPA technique (SALSA P050-CAH version C1, MRC Holland) evidenced by a 120 bp deletion in TNXB exon 35, which derives from TNXA pseudogene. We designed a PCR using a mixed oligonucleotide strategy to amplify a fragment of 5010 bp, considering pseudogene TNXA interference, and then all subjects were screened for other TNXB alterations related to CH-2 and CH-3 by exon 40, 41 and 43 Sanger sequencing. We performed clinical evaluation of connective tissue dysplasia associated with EDS in 17 unrelated probands, 3 CAH siblings and 13 parents that were available and in whom a TNXB alteration was found. All patients were evaluated for joint and skin abnormalities and always by the same examiner using major and minor criteria for the diagnosis of classical-like and hypermobile EDS (Malfait et al, 2017). The Beighton 9-point scoring system was used to evaluate generalized joint hypermobility (score ? 6 for pre-pubertal children and adolescents, ? 5 for pubertal men and women up to the age of 50 and ? 4 for those > 50 years of age). Structural cardiac evaluation was also performed by doppler color echocardiography.\nResults: A molecular strategy to assess copy number variations and genetic status of TNXB was developed. TNXA/TNXB CH-1 was found in 30/73 (41%) non-related alleles carriers of CYP21A2 gene deletion. In addition, CH-2 and CH-3 were found in 21/73 (29%) and 1/73 (1.5%) alleles, respectively. This means that 71% of alleles were found to carry a contiguous gene deletion that extended into TNXB gene. Out of 66 non-related patients that were homozygous or heterozygous for CYP21A2 gene deletion and were evaluated in this study for copy number variations of TNXB gene, the monoallelic form was found in 43 patients (65%), while 4 patients were found to have a biallelic form (6%, 2 were homozygous for CH-1 and 2 were compound heterozygous for CH-1 and CH-2). All patients with biallelic form had generalized joint hypermobility, hypermobility of small joints, severe skin hyperextensibility and easy bruising, and they had clinical features of EDS with more severe phenotype than monoallelic form, while cardiac abnormalities were found in both forms.\nConclusions: A high frequency of TNXB alterations was found in CYP21A2 deletion carrier alleles in our population. MLPA, PCR and Sanger sequencing techniques resulted effective to characterize TNXB deletion. We found clinical manifestations of Ehlers-Danlos syndrome in subjects with biallelic and monollelic forms but accurate genotype-phenotype correlation remains to be elucidated in this cohort. Based on the high frequency of TNXB alterations in CYP21A2 deletion carrier alleles found, we recommend to evaluate TNXB status in these patients, warranting assessment and follow-up of connective tissue dysplasia including cardiologic alterations in positive cases. It would be important to expand the number of patients with cardiological evaluation in order to determine the incidence of structural and functional abnormalities in this cohort. Lastly, we found significant evidence in order to establish this molecular strategy in our hospital to evaluate congenital adrenal hyperplasia patient carriers of CYP21A2 gene deletion.